2015
DOI: 10.1530/rep-14-0403
|View full text |Cite
|
Sign up to set email alerts
|

Identification and differential expression patterns of porcine OCT4 variants

Abstract: OCT4 encoded by POU5F1 has a crucial role of maintaining pluripotency in embryonic stem cells during early embryonic development and several OCT4 variants have been identified in mouse and human studies. The objective of this study was to identify different variants of OCT4 and analyze their expression patterns in preimplantation porcine embryos and various tissues. In this study, we showed that POU5F1 transcribes its three variants, namely OCT4A, OCT4B, and OCT4B1. The OCT4B transcript consists of exons ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Previous reports showed that Oct4 retained several expressed pseudogenes and alternative splicing variants (Guo et al, ; Scarola et al, ). Though Oct4b1 was a lately discovered Oct4 splicing variant in human and other animal (Atlasi et al, ; Farashahi Yazd et al, ; Hwang et al, ), it was not reported in mouse yet. And the Oct4 splicing variants reported in mouse were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that Oct4 retained several expressed pseudogenes and alternative splicing variants (Guo et al, ; Scarola et al, ). Though Oct4b1 was a lately discovered Oct4 splicing variant in human and other animal (Atlasi et al, ; Farashahi Yazd et al, ; Hwang et al, ), it was not reported in mouse yet. And the Oct4 splicing variants reported in mouse were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Though Oct4b1 was a lately discovered Oct4 splicing variant in human and other animal (Atlasi et al, 2008;Farashahi Yazd et al, 2011;Hwang et al, 2014), it was not reported in mouse yet. And the Oct4 splicing variants reported in mouse were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Virus titration was performed by calculating the integrated copy numbers in HEK293-LTV cells inoculated with the prepared virus. To calculate copy numbers of integrated vectors and genomes, a linear-regression plot was prepared following our previous report [ 21 ]. Human genomic region ( hGAPDH ) and internal ribosome entry site (IRES) in lentiviral vector plasmids were assessed to calculate the number of integrated transgenes in the genome.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in present study, we aimed to examine whether overexpression of OCT4A , which has been reported to be pluripotent gene and major variant of OCT4A gene in pigs [ 21 ], could affect expression of X-linked genes regulating XCI in female porcine preimplantation embryos.…”
mentioning
confidence: 99%
“…These variants can form protein-protein interactions that could lead to developmental state-specific regulatory networks, thereby increasing the biological complexity compare to a single locus. For instance, Oct4 has more than two splice variants, in which Oct4A is expressed in ESCs and iPSCs, while Oct4B is expressed in differentiated cells and somatic tissues [32][33][34] . In this study, we found that porcine SALL4B was globally expressed in somatic tissues and cells, however, SALL4A was only detected in piPSCs, but was undetectable in muscle and liver tissues.…”
Section: Identification Of Porcine Sall4 Splicing Variantsmentioning
confidence: 99%